Effect of temperature on multiple competitive processes for co-production of carbon nanotubes and hydrogen during catalytic reforming of toluene. (15th March 2020) - He, Limo; Liao, Guang; Hu, Song; Jiang, Long; Han, Hengda; Li, Hanjian; Ren, Qiangqiang; Mostafa, Mohamed E.; Hu, Xun; Wang, Yi; Su, Sheng; Xiang, Jun
Graphical abstract: Highlights: H2 yield increased by 7 times while its purity decreased 5% from 500 °C to 800 °C. Coke amount initially increased to maximum at 650 °C then remarkably decreased. High temperature enhanced conversion of amorphous carbon to improve CNTs quality. Almost no CNTs generated at 800 °C due to the sintering of Ni crystallite. Abstract: The effects of reaction temperature (range from 500 °C to 800 °C) on multiple competitive processes were studied for the co-production of hydrogen and carbon nanotubes (CNTs) during catalytic reforming of toluene over Ni/α-Al2 O3 . With the temperature raising from 500 to 800 °C, H2 yield increased by 7 times while H2 proportion slightly decreased 5 vol% due to the competitive effect between steam reforming and reverse water–gas shift (WGS) reaction. Coke amounts (including amorphous carbon and CNTs) firstly increased and then decreased, which was determined by the competitive rate of formation and consumption reaction. Detailed characterization indicated the yield and quality of CNTs improved with the temperature increasing from 500 to 650 °C and reached the maximum at 650 °C, resulting from the enhancing transformation from amorphous to CNTs and consumption of amorphous carbon by steam. However, the growth of CNTs was suppressed by further increasing temperature, and almost no CNTs were generated at 800 °C. The higher temperature aggravated the sintering of Ni and enlarged their particle size, which was not conduced to CNTs growth.